Association between systemic inflammatory response index and bone turnover markers in Chinese patients with osteoporotic fractures: a retrospective cross-sectional study - Zhou, Peng; Lu, Ke; Li, Chong; Xu, Min-zhe; Ye, Yao-wei; Shan, Hui-qiang; Yin, Yi (Frontiers in Medicine, 2024)
Background The systemic inflammatory response index (SIRI) is a novel composite biomarker of inflammation. However, there is limited information on its use in the context of osteoporotic fractures. Hence, this study aimed to investigate the association between baseline SIRI values and bone turnover markers (BTMs) in Chinese patients diagnosed with osteoporotic fractures (OPFs), to offer a more precise method for assessing bone health and inflammation in clinical settings. Methods A retrospective cross-sectional study was conducted on 3,558 hospitalized patients with OPFs who required surgery or hospitalization at the First People’s Hospital of Kunshan City from January 2017 to July 2022. Baseline measurements of SIRI, β-CTX (beta-C-terminal telopeptide of type I collagen), and P1NP (procollagen type I N-terminal propeptide) were obtained. The analyses were adjusted for variables, including age, sex, body mass index (BMI), and other initial laboratory and clinical findings. Furthermore, multivariable logistic regression, smooth curve fitting, and threshold analysis were also performed. Results The results revealed a negative correlation between baseline SIRI values and both β-CTX and P1NP levels. After adjusting for covariates in the regression analysis, each unit increase in SIRI was found to be inked to a reduction of 0.04 (β = −0.04; 95% confidence interval [CI], −0.05 to −0.03; with p-value <0.001) in β-CTX levels and a decrease of 3.77 (β = 3.77; 95% CI, 5.07 to 2.47; with p-value <0.001) in P1NP levels. Furthermore, a curvilinear relationship and threshold effect were also identified. Turning points were identified at SIRI values of 1.41 and 1.63 on the adjusted smooth curve. Conclusion The results showed a negative correlation between the baseline SIRI value and β-CTX level, as well as the level of P1NP. This suggests a possible link between the systemic inflammatory response and reduced bone metabolism. If these findings are verified, SIRI has the potential to function as a predictive indicator for BTMs. Nevertheless, additional research is necessary to verify these findings.